Organizational structure as the channeling of boundedly rational pre-play communication - Tore Ellingsen; Robert Östling (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
We model organizational decision making as costless pre-play communication. Decision making is called authoritarian if only one player is allowed to speak and consensual if all players are allowed to speak. Players are assumed to have limited cognitive capacity and we characterize their behavior under each decision making regime for two different cognitive hierarchy models. Our results suggest that authoritarian decision making is optimal when players have conflicting preferences over the set of Nash equilibrium outcomes, whereas consensual decision making is optimal when players have congruent preferences over this set. The intuition is that authoritarian decision making avoids conflict, but sometimes creates insufficient mutual trust to implement socially optimal outcomes.
Keywords: C72; L20; M21; M54; 330; Organizational decision making; coordination games; communication; cognitive hierarchy models; Kommunikation; Entscheidungstheorie; Organisation; Konflikt; Spieltheorie